2010
DOI: 10.1071/bt09213
|View full text |Cite
|
Sign up to set email alerts
|

Differential biochemical responses of Calliandra brevipes (Fabaceae, Mimosoidae) to galling behaviour by Tanaostigmodes ringueleti and T. mecanga (Hymenoptera, Tanaostigmatidae)

Abstract: Two species of Tanaostigmodes, T. ringueleti and T. mecanga, induce two distinct gall morphotypes in Calliandra brevipes Benth. (Fabaceae: Mimosoidae), namely a globose and a fusiform one. Secondary and primary metabolism of the two galls was compared with that of the stem tissue of the host plant. Phytochemical screening of gall samples revealed that triterpenoids were exclusive of the globose gall, and sterols exclusive of the fusiform gall, whereas saponins were absent in both galls. Flavonoid content in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…This competition can also be decisive for the establishment of chemical patterns in plant galls. Studying the galling behavior of two species of Tanaostigmodes (T. ringueleti and T. mecanga) that induce two distinct gall morphotypes on Calliandra brevipes, Detoni et al [27] observed that the primary and secondary metabolism of galls differentially favored the production of nutritional metabolites over defensive ones. The gall morphotype with the largest number of inducers per chamber (T. ringueleti gall) has the lowest concentration of flavonoids, but accumulates the highest amounts of carbohydrates and proteins, thus supporting the nutritional hypothesis for the adaptive value of the galling habit [81].…”
Section: Phenolics Accumulation Follows Ros Signaling At Gall Sitesmentioning
confidence: 99%
“…This competition can also be decisive for the establishment of chemical patterns in plant galls. Studying the galling behavior of two species of Tanaostigmodes (T. ringueleti and T. mecanga) that induce two distinct gall morphotypes on Calliandra brevipes, Detoni et al [27] observed that the primary and secondary metabolism of galls differentially favored the production of nutritional metabolites over defensive ones. The gall morphotype with the largest number of inducers per chamber (T. ringueleti gall) has the lowest concentration of flavonoids, but accumulates the highest amounts of carbohydrates and proteins, thus supporting the nutritional hypothesis for the adaptive value of the galling habit [81].…”
Section: Phenolics Accumulation Follows Ros Signaling At Gall Sitesmentioning
confidence: 99%
“…Some phytohormones such as auxin and cytokinins, which stimulate cell growth and division, have been described in larval salivary secretions and in secretions injected by insects during oviposition [ 14 , 16 ]. Moreover, salivary proteins and peptides probably play a role in gall induction since their expression is detected in galled tissues [ 19 , 20 ]. However, the mechanisms leading to gall formation are still poorly understood [ 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Em flores de Hypericum perforatum observou-se o aumento na concentração de flavonoides, hipericinas e ácido clorogênico (Gray et al, 2003). Os fenóis contribuem para a absorção e neutralização de radicais livres gerados pelo aumento do estresse oxidativo nas plantas provocado pelo déficit hídrico (Detoni et al, 2010). Resultados similares foram observados por Formiga et al (2009), que indicaram o impacto de fatores físicos na produção de fenóis em folhas sadias e com galhas de Aspidosperma spruceanum.…”
Section: Resultsunclassified